Hungarian Monitoring, 7 February 1990 . [Magyar rádiófigyelő], 1990. február 7 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USSR: CPSU Central Committee meeting; Gorbachev recommends abolition of the one-party system, Baker's visit to Moscow - US foreign minister Baker's speech in Prague - Neo-Fascist protest in Leipzig - German-German negotiations: financial union - Soviet troop withdrawals from Czechoslovakia Domestic Affairs: - Hungarian-Vatican diplomatic negotiations - Question of Hungarian neutrality - National summit meeting - State and party leaders' property declarations - Minutes of Cardinal Mindszenty's hearing - Election programs Economy: - Trade minister's press conference Külpolitika: - SZU: SZKP KB ülés; Gorbacsov javasolta az egypártrendszer eltörlését, Baker moszkvai látogatása - Baker külügyminiszter prágai beszéde - Lipcsei újfasiszta tüntetés - Német-német tárgyalások; a pénzügyi unió - Csehszlovákiai szovjet csapatok kivonása Belpolitika: - Magyar-vatikáni diplomáciai tárgyalások - A magyar semlegesség kérdése - Nemzeti csúcstalálkozó - Állami és pártvezetők vagyonnyilatkozata - Mindszenty bíboros kihallgatási jegyzőkönyve - Választási műsorok Gazdaság: - A kereskedelmi miniszter sajtótájékoztatója